Sclerotherapy with 3% polidocanol foam to treat second‐degree haemorrhoidal disease: Three‐year follow‐up of a multicentre, single arm, IDEAL phase 2b trial. (9th November 2022) - Gallo, Gaetano; Picciariello, Arcangelo; Pietroletti, Renato; Novelli, Eugenio; Sturiale, Alessandro; Tutino, Roberta; Laforgia, Rita; Moggia, Elisabetta; Pozzo, Mauro; Roveroni, Maurizio; Bianco, Vincenzo; Realis Luc, Alberto; et al.
Abstract: Background: Sclerotherapy with 3% polidocanol foam is becoming increasingly popular for the treatment of symptomatic I–II or III degree haemorrhoidal disease (HD). However, there are no studies that have reported a follow‐up of more than 1 year. The purpose of this study was to analyse the long‐term outcomes of sclerotherapy with 3% polidocanol foam in the treatment of II–degree HD. Methods: This was an open label, single‐arm, phase 2b trial conducted in 10 tertiary referral centres for HD. A total of 183 patients with II–degree HD, aged between 18 and 75 years with symptomatic HD according to the Goligher classification and unresponsive to medical treatment, were included in the study and underwent sclerotherapy with 3% polidocanol foam. The efficacy was evaluated in terms of bleeding score, haemorrhoidal disease symptom score (HDSS) and short health scale for HD (SHS–HD) score. Successful treatment was defined as the complete absence of bleeding episodes after 7 days (T1) according to the bleeding score. Results: The overall success rate ranged from 95.6% (175/183) at 1 year to 90.2% (165/183) after the final 3 year follow‐up. The recurrence rate, based on the primary outcome, ranged from 12% (15/125) to 28% (35/125). The greatest increase in recurrence (15) was recorded between 12 and 18 months of follow‐up, then another five between 18 and 24 months. Both the HDSS and the SHS score remained statistically significant ( p  < 0.001) from a median preoperative value of 11 (10–13) and 18 (15–20) to 0 (0–2) and 4 (0–4), respectively. Symptom‐free (HDSS = 0) patients, excluding patients converted to surgery, increased from 55.5% (101/182) at 1 year to 65.1% at 3 years (110/169). There were no intraoperative complications in redo‐sclerotherapy nor additional adverse events (AEs) compared to the first 12 months. Conclusions: Sclerotherapy with 3% polidocanol foam is gradually establishing itself in the treatment of bleeding HD due to its repeatability, safety, convenience in terms of direct and indirect costs with the absence of discomfort for the patient as well as AEs rather than an excellent overall success rate.